What happens when patients require intensification from basal insulin? A retrospective audit of clinical practice for the treatment of type 2 diabetes from four Australian centres. Issue 3 (June 2015) - Fulcher, Gregory; Roberts, Anthony; Sinha, Ashim; Proietto, Joseph
Highlights: Insulin inertia remains a significant problem in Australia. On average, patients have type 2 diabetes mellitus for 11 years before starting insulin. HbA1c levels were above target and 40% of patients already had diabetic microvascular complications. By the time a new treatment was added to basal insulin, 61% of patients were not at FPG target. Individualised management strategies should focus on when to initiate insulin and how to adjust doses over time. Abstract: Aims: Little is known about clinical practices beyond the initiation of basal insulin in patients with type 2 diabetes mellitus (T2DM) in Australia. To determine the proportion of patients who progressed from basal insulin to each of three possible therapy groups: Group 1 addition of rapid-acting insulin, Group 2 switch to pre-mixed insulin, Group 3 addition of another therapy (incretin, glitazone, sulphonylurea, metformin, acarbose). Methods: Retrospective audit across four Australian hospital clinics. Patients had a diagnosis of T2DM, basal insulin had been initiated and a subsequent treatment intensification/change had occurred during the analysis period (September 2007–March 2012). Results: Patients were classified into one of three intensification groups for analysis: Group 1, 56.1% (111/198); Group 2, 22.7% (45/198) and Group 3, 21.2% (42/198). Prior to basal insulin initiation, mean T2DM duration was 11 years. Between starting basal insulin and treatment intensification, 42/183 (22.9%) patients achieved the HbA1c target of <7.0% (53 mmol/mol). Initiation of basal insulin provided temporary improvement in glycaemic control followed by subsequent deterioration. With further treatment intensification, only 40/180 (22.2%) patients achieved the HbA1c target of <7.0% (53 mmol/mol). Patients in the insulin groups gained weight (Group 1, rapid acting insulin, 1.9 ± 7.4 kg; Group 2, premixed insulin 2.3 ± 4.8 kg); those in Group 3 lost weight (−0.9 ± 13.54 kg). Hypoglycaemic episodes were uncommon irrespective of group. Conclusions: There is continued need for improved patient management; individualised strategies should focus on when to initiate insulin, how to adjust and optimise doses over time and, when required, the introduction of intensification regimens.